PEMODELAN STRUKTUR LOYALITAS PEL PEMODELAN STRUKTUR LOYALITAS PELANGGAN DI RSUD AWET MUDA NARMADA KABUPATEN LOMBOK BARAT - Sarwan Payanadi (Jurnal Medika Hutama, 2026)
In 2023, Awet Muda Narmada Regional General Hospital experienced a significant increase in customer visits compared to 2022. Outpatient services increased by 68.59 percent, while inpatient visits increased by 76.92 percent. Based on this, the researcher aimed to examine the extent of service quality, hospital customer value, and customer loyalty at Awet Muda Narmada Regional General Hospital. The purpose of this study was to identify the modeling structure of customer loyalty at Awet Muda Narmada Regional General Hospital. The number of respondents was 150 people. The respondent criteria in this study included: (1) patients registered as inpatients with a minimum length of stay of three days at Awet Muda Narmada Regional General Hospital; (2) patients registered as outpatients who had visited the hospital at least three times previously; (3) male or female patients aged at least 17 years who were registered in either the inpatient or outpatient department; and (4) patients who were conscious and willing to answer the questions. This study used a quantitative approach with the Structural Equation Modeling method using Partial Least Squares analysis. The results of the study concluded that service quality has a significant positive effect on customer loyalty; service quality also has a significant positive effect on customer value; customer value has a significant positive effect on customer loyalty; and the effect of service quality on customer loyalty can be mediated by customer value. The findings of this study can serve as a reference for the hospital in improving its services, which in turn can increase patient loyalty to the hospital